2021
DOI: 10.1038/s41598-021-84728-2
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and replicative cellular aging of the human placenta and chorioamniotic membranes

Abstract: Recent hypotheses propose that the human placenta and chorioamniotic membranes (CAMs) experience telomere length (TL)-mediated senescence. These hypotheses are based on mean TL (mTL) measurements, but replicative senescence is triggered by short and dysfunctional telomeres, not mTL. We measured short telomeres by a vanguard method, the Telomere shortest length assay, and telomere-dysfunction-induced DNA damage foci (TIF) in placentas and CAMs between 18-week gestation and at full-term. Both the placenta and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Interestingly, these investigators did not observe a corresponding decrease in mean telomere lengths in their term placental tissues; thereby confirming the limited utility of measuring average telomere lengths to assess changes in short telomeres. While our cohort was limited to the third trimester of pregnancy, our observation that even in the last weeks of human pregnancy, there is a significant increase in VST is consistent with the findings from Lai and colleagues [13]. One important difference between our current study and prior studies, including the one reported by Lai et al, is that the placental tissues in the prior studies were collected after the onset of labor [13,19], making it difficult to determine if the process of undergoing labor had any effect on telomere lengths.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, these investigators did not observe a corresponding decrease in mean telomere lengths in their term placental tissues; thereby confirming the limited utility of measuring average telomere lengths to assess changes in short telomeres. While our cohort was limited to the third trimester of pregnancy, our observation that even in the last weeks of human pregnancy, there is a significant increase in VST is consistent with the findings from Lai and colleagues [13]. One important difference between our current study and prior studies, including the one reported by Lai et al, is that the placental tissues in the prior studies were collected after the onset of labor [13,19], making it difficult to determine if the process of undergoing labor had any effect on telomere lengths.…”
Section: Discussionsupporting
confidence: 91%
“…Most prior work on telomeres in human placental tissue examined average telomere lengths and reported an average shortening of telomere length across pregnancy [ 7 , 9 , 10 ]. However, a recent study by Lai et al [ 13 ] has evaluated short telomere segments in human gestational tissues, observing a significant increase of telomere segments less than 3 kb in both term placentas and chorioamniotic membranes when compared to these same tissues obtained at 18 weeks of gestation. Interestingly, these investigators did not observe a corresponding decrease in mean telomere lengths in their term placental tissues; thereby confirming the limited utility of measuring average telomere lengths to assess changes in short telomeres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with the cord blood cells that are at early hematopoiesis and abundant in telomerase-expressing stem cells, placenta cells undergo cellular senescence such that they may have shortened TL (17). As the pregnancy progresses, telomerase activity in the placenta declines, resulting in shortened TL across gestation with the shortest telomeres at term (54,55), probably due to the increasing production of mediators, particularly pro-inflammatory cytokines, neutrophil recruitment chemokines, and arachidonic acid metabolites of chorioamniotic cells in the third trimester of pregnancy (56). However, few studies indicate a discrepancy in the results of TL in the cord blood compared to the placenta (19,57), and we found no differences in TL between the cord blood and the placenta in the current study.…”
Section: Discussionmentioning
confidence: 99%